Symbolic meanings and e-learning in the workplace: The case of an intranet-based training tool. Issue 2 (April 2014) - Michalski, Marina P
This article contributes to the debate on work-based e-learning, by unpacking the notion of 'the learning context' in a case where the mediating tool for training also supports everyday work. Users' engagement with the information and communication technology tool is shown to reflect dynamic interactions among the individual, peer group, organizational and institutional levels. Also influential are professionals' values and identity work, alongside their interpretations of espoused and emerging symbolic meanings. Discussion draws on pedagogically informed studies of e-learning and the wider organizational learning literature. More centrally, this article highlights the instrumentality of symbolic interactionism for e-learning research and explores some of the framework's conceptual resources as applied to organizational analysis and e-learning design.